Tatakrama Kepemimpinan Sunda dalam Novel Sejarah Tanjeur na Juritan Jaya di Buana Karya Yoseph Iskandar - Isnendes, Retty; Ruhaliah, Ruhaliah; Koswara, Dedi; Permana, Ruswendi (UPI, 2019)
There is a presumption that Sundanese people leadership is weak and feeble so they can not compete on the national level. Though history recorded some names of Sundanese leaders, such as Prabu Wangi, Prabu Niskala Wastu Kanca, and Sri Baduga Maharaja. In the literature, the name of King Siliwangi is an icon and symbol of the great and successful Sundanese leader of all time. The identity and symbolism of the Sundanese leader are also reflected in the historical novel of Tanjeur na Juritan Jaya di Buana written by Yoseph Iskandar. Uniquely, the novel relies on the manuscript of Prince Wangsakerta from Cirebon which in the 1980s appalled Indonesia history. The novel has been awarded Rancage from Ajip Rosidi's Rancage Foundation. By using descriptive method and literature review technique and interpretation, the novel will be examined his leadership ethics in ethno pedagogic scope. The aims of this study are: (a) to describe the principles of Sundanese leadership in the novel, (b) to describe the etnopedagogical aspect in the novel, and (c) to compare the leadership principles of the past and the present as models of cultural education. The expected outcomes are the descriptions of figures of Sundanese leadership, Sundanese leadership manners, and the cultural education model found in the novel analyzed.AbstrakAda anggapan bahwa kepemimpinan Sunda lemah sehingga tidak dapat bersaing di panggung nasional. Padahal sejarah mencatat sejumlah nama pemimpin panutan Sunda, misalnya saja Prabu Wangi, Prabu Niskala Wastu kancana, dan Sri Baduga Maharaja. Dalam tataran sastra nama Prabu Siliwangi merupakan ikonitas dan simbolitas pemimpin Sunda yang besar dan berhasil sepanjang masa. Ikonitas dan simbolitas pemimpin Sunda tergambar juga dalam novel sejarah Tanjeur na Juritan Jaya di Buana yang ditulis oleh Yoseph Iskandar. Unik dan utamanya, novel tersebut bersandar pada naskah Pangeran Wangsakerta dari Cirebon yang tahun 1980-an menggemparkan jagat kesejarahan Indonesia. Novel tersebut telah mendapat hadiah Rancage dari Yayasan Rancage Ajip Rosidi. Dengan menggunakan metode deskriptif dan teknik telaah pustaka dan interprerasi, novel tersebut akan dikaji tatakrama kepemimpinannya dalam lingkup etnopedagogik. Tujuan penelitian ini adalah untuk: (a) mendeskripsikan tatakrama kepemimpinan Sunda dalam novel, (b) mendeskripsikan aspek etnopedagogik dalam novel, dan (c) membandingkan tatakrama kepemimpinan masa lalu dan masa sekarang sebagai model pendidikan budaya. Hasil yang diharapkan adalah terdeskripsikannya tokoh-tokoh dalam kepemimpinan Sunda, tatakrama kepemimpinan Sunda, dan model pendidikan budaya dari novel yang dianalisis.